LINGUISTIC DIVERGENCE OF DAYAK NGAJU AND KADORIH: A DIALECTOMETRIC AND CULTURAL PERSPECTIVE - Dwisetyo, Vici; Perkasa, Ikhlas Abdi; Endriyanto, Beny; Annida, Raviona; Aisyah, Risfa Nur (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2023)
This study explores the linguistic relationship between Dayak Ngaju (DN) and Kadorih (BK), two languages spoken within the Dayak communities of Borneo. Despite their shared Austronesian origin, DN and BK have diverged significantly over time due to geographic, cultural, and social factors. Using a qualitative approach, the research employed interviews, observations, and document analysis to examine their kinship and divergence. Vocabulary comparison using the Swadesh list revealed an 87.5% difference, classifying DN and BK as distinct languages according to Guiter’s (1973) dialectometric scale. Interviews and observations highlighted BK’s role in preserving ancestral traditions and DN’s adaptation to modern social contexts, underscoring their distinct linguistic and cultural functions. The findings emphasize the dynamic interplay between language evolution and cultural identity, providing insights into the linguistic diversity of the Dayak heritage. This research contributes to broader discussions on Austronesian language classification and offers a deeper understanding of the socio-cultural dynamics shaping language development.